Floristic diversity on the early medieval earthworks of Chełmno Land (Ziemia Chełmińska) in NW Poland - Kamiński, Dariusz (Biodiversity: Research and Conservation, 2006)
This study aimed at comparing the flora of 29 early medieval earthworks, characterised by various degrees of anthropogenic transformation, in order to demonstrate their role as refuges of rare plant species. The earthworks were classified according to their index of total synanthropization (WSc), which was assumed to indicate the level of floristic transformation. The highest floristic diversity was observed on the earthworks exposed to moderate human impact, due to fragmentation of phytocoenoses. The high floristic diversity and sites of rare heliophilous species are threatened by the discontinuity of traditional forms of land use, i.e. grazing.